Identification of novel OXA-134-like β-lactamases in Acinetobacter lwoffii and Acinetobacter schindleri isolated from chicken litter - Mlynarcik, Patrik; Bardon, Jan; Htoutou Sedlakova, Miroslava; Prochazkova, Petra; Kolar, Milan (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2019)
BACKGROUND: Various food-producing animals have been recognized in recent years as a potential reservoir for the spread of antibiotic resistant bacteria that may pose a risk to human health and therefore their dissemination in the food production chain needs to be assessed. METHODS: In this study, 450 boot swabs from chicken farms were analyzed for the presence of antimicrobial resistance with a focus on β-lactams resistance in Acinetobacter species. RESULTS: Two β-lactamase-encoding genes were first time identified in Acinetobacter lwoffii and Acinetobacter schindleri isolates. The deduced amino acid sequence of OXA-496 shared 93.8% identity with OXA-363. The second OXA-134-like enzyme, OXA-537, had the highest sequence identity (97.8%) with OXA-235 and OXA-237. CONCLUSIONS: The results of this study illustrate the occurrence of new OXA-134-like β-lactamases, called OXA-496 and OXA-537, carrying strains of Acinetobacter lwoffii and Acinetobacter schindleri in chicken farm litter, and highlight the possible role of Acinetobacter as a reservoir of resistance genes.
Keywords: Microbial Sensitivity Tests; beta-laktamová rezistence; beta-Lactam Resistance; identification; Chickens; mikrobiální testy citlivosti; zvířata; chicken; Acinetobacter; β-lactamase; antibiotics; beta-laktamasy; kur domácí; Drug Resistance, Bacterial; Czech Republic; Farms; beta-Lactamases; bakteriální léková rezistence; Animals; Česká republika; resistance; farmy